Cystathionine β-synthase deficiency in the E-HOD registry-part I: pyridoxine responsiveness as a determinant of biochemical and clinical phenotype at diagnosis - Kožich, Viktor; Sokolová, Jitka; Morris, Andrew A. M.; Pavlíková, Markéta; Gleich, Florian; Kölker, Stefan; Krijt, Jakub; Dionisi-Vici, Carlo; Baumgartner, Matthias R.; Blom, Henk J.; Huemer, Martina (Journal of inherited metabolic disease, 2021)
Cystathionine β-synthase (CBS) deficiency has a wide clinical spectrum, ranging from neurodevelopmental problems, lens dislocation and marfanoid features in early childhood to adult onset disease with predominantly thromboembolic complications. We have analysed clinical and laboratory data at the time of diagnosis in 328 patients with CBS deficiency from the E-HOD (European network and registry for Homocystinurias and methylation Defects) registry. We developed comprehensive criteria to classify patients into four groups of pyridoxine responsivity: non-responders (NR), partial, full and extreme responders (PR, FR and ER, respectively). All groups showed overlapping concentrations of plasma total homocysteine while pyridoxine responsiveness inversely correlated with plasma/serum methionine concentrations. The FR and ER groups had a later age of onset and diagnosis and a longer diagnostic delay than NR and PR patients. Lens dislocation was common in all groups except ER but the age of dislocation increased with increasing responsiveness. Developmental delay was commonest in the NR group while no ER patient had cognitive impairment. Thromboembolism was the commonest presenting feature in ER patients, whereas it was least likely at presentation in the NR group. This probably is due to the differences in ages at presentation: all groups had a similar number of thromboembolic events per 1000 patient-years. Clinical severity of CBS deficiency depends on the degree of pyridoxine responsiveness. Therefore, a standardised pyridoxine-responsiveness test in newly diagnosed patients and a critical review of previous assessments is indispensable to ensure adequate therapy and to prevent or reduce long-term complications.
Online published: 09 December 2020
Gesehen am 09.11.2023